2014
DOI: 10.1186/1471-2164-15-995
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome sequencing of two wild barley (Hordeum spontaneum L.) ecotypes differentially adapted to drought stress reveals ecotype-specific transcripts

Abstract: BackgroundWild barley is adapted to highly diverse environments throughout its geographical distribution range. Transcriptome sequencing of differentially adapted wild barley ecotypes from contrasting environments contributes to the identification of genes and genetic variation involved in abiotic stress tolerance and adaptation.ResultsTwo differentially adapted wild barley ecotypes from desert (B1K2) and Mediterranean (B1K30) environments were analyzed for drought stress response under controlled conditions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 81 publications
0
34
0
Order By: Relevance
“…A number of unique transcripts were identified in the wild barley, and of the SNPs identified, the desert ecotype had a higher proportion of nonsynonymous SNPs. These data are a valuable genomic resource for barley genomics and barley breeding (Bedada et al ., ).…”
Section: Genomics Of Cwrsmentioning
confidence: 97%
“…A number of unique transcripts were identified in the wild barley, and of the SNPs identified, the desert ecotype had a higher proportion of nonsynonymous SNPs. These data are a valuable genomic resource for barley genomics and barley breeding (Bedada et al ., ).…”
Section: Genomics Of Cwrsmentioning
confidence: 97%
“…spontaneum) populations sampled from a wide adaptive niche across Israel (Hubner et al, 2009). Since its establishment, it has become a foundational resource for studying plant adaptation and evolution, including the investigation of populations' behaviour under different environments (Bedada et al, 2014;Galkin et al, 2018;Hübner et al, 2012;Hübner et al, 2013). The period length and amplitude of the circadian rhythms are two traits that were found to be correlated with temperature and soil organic matter at the collection sites, respectively (Dakhiya et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Transcriptomic analysis is an effective approach to identify drought stress related genes, pathways, and processes. The studies on molecular mechanisms of drought tolerance using transcriptomic analysis have been reported extensively in many plants [ 15 20 ], including wheat [ 21 ], wild emmer wheat [ 22 , 23 ] and wild barley [ 24 , 25 ]; however, little is known about the Tibetan hulless barley. Recently, Zeng et al demonstrated changes in the gene expression patterns of well-watered, water deficit, and final water recovery stages in hulless barley.…”
Section: Introductionmentioning
confidence: 99%